Genetic control of boron efficiency in wheat (Triticum aestivum L.) - Jamjod S. (2014)
The genetic control of boron (B) efficiency in wheat (Triticum aestivum L.) was studied for three genotypes representing B inefficient (I, Bonza), moderately B inefficient (MI, SW 41) and B efficient (E, Fang 60) categories. Boron efficiency was expressed as a partially dominant character but the phenotypes of F1 hybrids, relative to parents, indicated genetic control varying from recessive to additive to completely dominant with different cross combinations and B levels. Major genes were identified from the evaluation of F2-derived F3 populations derived from intercrosses between the three parents. Monogenic segregation was found in Bonza x SW 41 and SW 41 x Fang 60 crosses and digenic segregation resulted in Bonza x Fang 60. Among the three wheat genotypes with widely different B efficiency, genetic variation for response to B could be accounted for by two genes, Bod1 and Bod2.